Management of anaemia in oncohaematological patients treated with biosimilar epoetin alfa: results of an Italian observational, retrospective study. (January 2017) - Rosti, Giovanni; Petrini, Mario; Bosi, Alberto; Galieni, Piero; Bernardi, Daniele; Giglio, Gianfranco; Dorotea, Laura; Falini, Brunangelo; Scelzi, Elvira; Veltri, Enzo; Castelli, Roberto; Longagnani, Chiara; et al.
Background: Many patients with solid tumours or nonmyeloid haematopoietic tumours develop symptomatic anaemia, which has a major impact on quality of life (QoL). The efficacy of erythropoiesis-stimulating agents (ESAs) in improving QoL and reducing blood transfusions has been widely demonstrated. Binocrit® (biosimilar epoetin alfa) is an ESA indicated in the European Union for treating chemotherapy-induced anaemia. The aim of this study was to investigate the effect of Binocrit® on haemoglobin (Hb) levels in anaemic cancer patients in Italian clinical practice. Methods: The ANEMONE study was a national, longitudinal, retrospective, multicentre observational study. Patients had to be 18 years or older, with a solid tumour or non-Hodgkin's lymphoma, Hodgkin's disease or multiple myeloma, receiving chemotherapy, and treated with Binocrit® to manage chemotherapy-induced anaemia. The primary outcomes were the proportion of patients with a Hb increase ⩾1 g/dl during the first 4 weeks and with a Hb increase ⩾2 g/dl during the first 12 weeks. Results: A total of 245 patients were enrolled and 215 patients were evaluable for statistical analysis. In the first 4 weeks, 49.3% of patients showed an increase in Hb of ⩾1 g/dl: 45.5% in patients with solid tumours and 52.1% in patients with haematological malignancies. In the first 12 weeks, 51.6% of patients showed an increase in Hb of ⩾2 g/dl (48.4% solid tumours, 54.2% haematological diseases). Treatment with Binocrit® was well tolerated. Conclusions: These results confirm the effectiveness and safety of Binocrit® for chemotherapy-induced anaemia in routine practice in patients with solid tumours, lymphoma and myeloma.